The East Java Veterans National Development University's admissions decision-support system for non-PNS lecturers - Nadim; Jusak; I Gusti Ngurah Alit Widana Putra (INFOTECH : Jurnal Informatika & Teknologi, 2023)
Universitas Pembangunan Nasional Veteran Jawa Timur merupakan salah satu Universitas Negeri di kota surabaya. Universitas Pembangunan Nasional Veteran ini memiliki Program Sarjana (S1), Program magister (S2), Universitas Pembangunan Nasional (UPN) Veteran East Java is one of the State Universities in the city of Surabaya. Universitas Pembangunan Nasional Veteran has a Bachelor Program (S1), Master Program (S2), Doctoral Program (S3). Every certain period the University opens job vacancies to find Educators (Lecturers). The selection stage consists of basic ability tests, field ability tests, teaching ability tests, and interviews. Unfortunately, to decide who is a prospective lecturer who is accepted as a new lecturer, you have to wait approximately two weeks because the results of each stage still have to be calculated first by the committee and have not used the Decision Support System. The method to be used in this study is Simple Additive Weighting which is one method in supporting decisions. Data collection was carried out by means of interviews and observations as well as literature studies to support this research. The result of this study is the application of a decision support system that can help the selection of non-civil servant lecturer admissions that can be used for consideration by decision makers by the University of National Development of East Java Veterans to decide who are the prospective lecturers who pass or not in the selection in a shorter time than before.